Labour Supply and Earning Functions of Educated Married Women: A Case Study of Northern Punjab (The Pakistan Development Review, 2007)
This study analyses labour supply of educated married women in Mandi Bahauddin, a typical district of northern Punjab in Pakistan. The study finds that the education level and economic compulsion are important factors affecting women’s labour force participation decision. But, otherwise, they are independent in their decision-making, e.g., the women living in joint families or those with less educated husbands and/or parents are not socially constrained in terms of participation. Human capital variables like education, experience, and training, besides the nature of occupation and distance from the central city, are the important factors affecting women’s earning rates, while the hours of work are mainly determined institutionally.